Modeling User Perception of Interaction Opportunities in Collaborative Human-Computer Settings - Kamar, Ece; Grosz, Barbara J; Sarne, David (In Proceedings of AAAI 2007, Student Abstract and Poster Program, 2007)
Interruptions are important for effective collaborative work, because agents often possess information required by others on their team. This need to get information from another agent arises in mixed human-computer teams as well as in homogeneous computer-agent environments. For example, a (human) driver may see changes in weather conditions that affect route selection while an automated navigation system without sensors does not. The navigation system may need this information to identify the best route. It is crucial to time interruptions, which are inherently disruptive, appropriately. Efficient interruption timing improves task performance as well as emotional state and awareness of the user, and decreases the negative effects of interruption (Adamczyk & Bailey 2004).